O exame de papanicolau na estratégia saúde da família - Barros, Sara Virna Alves (2019)
Objective: To discuss the Pap smear through the perceptions of nurses of the Family Health Strategy (FHS) in a capital of northeastern Brazil. Methodology: This is a descriptive case study with a qualitative method, conducted with nurses working in the Family Health Strategy in the city of Recife, PE. Data collection took place from January 28 to February 28, 2019, through an online questionnaire sent by email. Data analysis was performed using the ALCESTE software. After this analysis, the Elementary Context Units (ECU) of each of the identified classes were submitted to a careful content analysis. The project was approved by the Research Ethics Committee, protocol number 2.924.765. Results: From the report of nurses, potentialities regarding the collection of Pap smears were evidenced, such as health education activities, the longitudinal and integral follow-up of women, as well as their ease of geographical proximity to the Basic Health Unit. In addition, the collection of the exam is organized by the Family Health Teams on days previously set with scheduling by spontaneous demand, extending this assistance also in night shifts on commemorative dates and in campaigns, favoring the attraction of women. Some weaknesses were pointed out by the nurses about the exam, such as ignorance about the purpose of the procedure, fear, partner interference and shame, as well as discourses associated with the management of the work process. Conclusion: It was concluded that effective health education, organization of supply and longitudinal and integral follow-up of users are facilitating factors for the examination. However, the scarcity of materials and inputs, the long timeframe for delivery of the exam’s result, as well as the negative stigmas and experiences result in the women's refusal to perform the test. Therefore, it is necessary to sensitize users not only to perform the exam, but to also develop educational practices in accordance with the reality of this public. In addition, the management should organize the flow of materials and inputs and provide users with a supportive network for the diagnosis of precursor lesions of structured and resolute cervical cancer.